(untitled) (Journal of Educational and Psychological Sciences, 2018)
The aim of this study was to investigate the effect of teaching binary forms using the GeoGebra program on the achievement of the first grade students. The study was limited to the level of understanding and remembering. The researchers used the semi-experimental approach, which is based on the design of the experimental and equal control groups with tribal and remote measurement. The study population consists of students of the first grade intermediate in the school of Subt al-Jarah in Qunfudah governorate for the academic year 1438/1439 AH (54 students) , of whom 29 are students In the control group, (25) students of the experimental group, which was studied using the program of GeoGabra for the lessons of binary forms, and the study found that there are differences in total achievement and at the first two levels of the classification of Bloom, the memory and understanding, between the experimental group and obtained a general average (26.60) (30) , and (16.34) and the difference between them (10.26) by (34.2%) for the benefit of the experimental group. The researchers recommended using the GeoGabra program to teach binary forms, rather than the traditional method.